Statement I) a*b = b*a => a + b - ab = b + a - b Hence this is true.

Statement II) a*0 = a

Solve LHS

=> a + 0 - a.0 = a

Hence this is true

Statement III) (a*b)*c = a*(b*c)

Simplify LHS

=> ( a + b - ab) * c

=> a + b - ab + c - (a + b - ab)c

=> a + b - ab + c - ac - bc + abc

=> a + b + c - ab - ac - bc + abc

Simplify RHS

=> a * ( b + c - bc)

=> a + b + c - bc - a(b+c -bc)

=> a + b + c - bc - ab -ac + abc

=> a + b + c - ab - ac - bc + abc

LHS = RHS

Hence This statement is true.

Answer is E

## Please log in or register to add a comment.